Improving Competitive Advantage and Business Performance through the Development of Business Network, Adaptability of Business Environment and Innovation Creativity: An Empirical Study of Batik Small and Medium Enterprises (SME) in Pekalongan, Central Ja - Meutia . (Aceh International Journal of Social Science, 2013)
Abstract - The purpose of this study is to observe how the business network, adaptability on business environment, and innovation creativity simply affect the competitive advantage and business performance of Batik SME in Pekalongan, Central Java, Indonesia. This study uses Structural Equation Modelling as multivariate analyses tool. AMOS software 16 was used as the aid tool to solve the problem in Structural Equation Modelling (SEM) application. Respondents in this study were the owner and manager of Small to Medium Sized Enterprises of batik industry in Pekalongan, Central Java, Indonesia. The testing result showed that innovation creativity has insignificant influence on competitive advantage; the adaptability of business environment has insignificant influence on competitive advantage; business network significantly affected competitive advantage; competitive advantage significantly influenced the SME business performance. The ability of entrepreneurs to build business network has eased an information exchange and also to make a social relatedness in order to improve the competitive advantage. The result of the study provides contribution to Resources-Based View (RBV) theory, where the companies were able to improve all their capabilities in enhancing the competitive advantage and SME’s performance. Keywords : Business network; Adaptability on business environment; Innovation creativity; Competitive Advantage; Business Performance; SMEPaper Type : Research Paper